Eosinophilic inflammation in hereditary angioedema: a single-center real-world retrospective chart review study - Boch, Katharina; Ludwig, Ralf J.; von Bubnoff, Dagmar; Recke, Andreas (Frontiers in Immunology, 2026)
BackgroundHereditary angioedema (HAE) is a rare genetic disorder characterized by recurrent, unpredictable swelling attacks primarily driven by bradykinin-mediated vascular permeability. However, additional inflammatory mechanisms may contribute to disease heterogeneity. During routine diagnostics, we observed elevated serum eosinophil cationic protein (ECP) levels in HAE patients, suggesting increased eosinophil activation. To date, eosinophil involvement in HAE has not been systematically investigated, this study aimed to validate clinical observations and explore a potential link between bradykinin signaling and eosinophilic inflammation.MethodsWe retrospectively analyzed data from 48 patients with confirmed HAE (32 HAE type I/II, 16 HAE with normal C1-INH) and 1,880 control patients treated at a tertiary university allergy and angioedema referral center. Using causal-inference Bayesian multilevel regression with bias-breaking post-stratification and propensity-score inverse probability weighting, we estimated the effect of HAE on serum ECP levels and absolute eosinophil counts while adjusting for age, sex, season, and allergic comorbidities.ResultsHAE was associated with a 1.52-fold average increase in serum ECP levels (most conservative 95% credibility interval: 1.24–1.90; Bayesian p = 0.00088), consistent across all modeling specifications. Absolute eosinophil counts were not elevated, indicating enhanced eosinophil activation independent of cell number.ConclusionsPatients with HAE show biochemical evidence of increased eosinophil activation, suggesting a previously unrecognized inflammatory component beyond bradykinin-driven edema formation. Further studies should clarify clinical implications and the potential contribution to comorbidities and phenotypic variability.